(untitled) (REMUNOM, 2025)
Acne is a clinical condition characterized by chronic inflammation of the skin, common mainly in young people during puberty. One of the treatment options is oral isotretinoin, sold as Roaccutane®. Isotretinoin shows good results by reducing sebum production by the sebaceous glands, thus preventing the formation of acne. However, the use of this medication is associated with a series of adverse effects. Thus, despite improving patients’ skin, this medication can cause other skin, mucosal and systemic problems, which raises concerns among physicians and also among pharmacists who fill these prescriptions. The objective of this study was to comprehensively and critically analyze the problems of isotretinoin in the treatment of acne, exploring the consequences of its use, administration protocols and safety considerations for the patient. An integrative review was carried out using Google Scholar as the initial search platform and the selected papers were from platforms such as Scielo, AcervoMais and EmNuvens. A total of 10 studies were selected and, according to the authors, the main adverse reactions cited were dry skin and mucous membranes. Other adverse reactions include laboratory changes such as increased cholesterol, triglycerides and liver enzymes, photosensitivity, teratogenicity, and possible depression, although this is an adverse effect that has been studied. Although isotretinoin presents various adverse reactions, it is still a safe and effective therapy for treating acne. However, care must be taken with the dose and duration of treatment for patients. Therefore, it is important to have pharmaceutical monitoring to access information on adverse reactions, thus avoiding unnecessary discontinuation of the medication or more serious complications.